Profile of Lumbar Spinal Stenosis Patients at Dr. M. Djamil Central Public Hospital from 2018-2022 - Akbar, Inasa Faiza; Sahputra, Roni Eka; Elfi, Eka Fithra; Rahmadian, Rizki; Rusjdi, Dina Arfiani; Silvia, Nelmi (Universitas Airlangga, 2024)
Background: Lumbar Spinal Stenosis (LSS) is a pathological condition characterized by narrowing of the spinal canal in the lower back. In Indonesia, comprehensive data on LSS is currently unavailable. This study aimed to determine the profile of LSS patients at Dr. M. Djamil Central Public Hospital. Methods: This descriptive cross-sectional study utilized medical record data from 122 LSS patients at Dr. M. Djamil Central Public Hospital between 2018 and 2022, selected via consecutive sampling. Inclusion criteria included age over 18 years and a confirmed LSS diagnosis. Exclusion criteria included incomplete medical records, lack of MRI results, and follow-up visits without treatment. Univariate analysis was performed using SPSS 25.0 to describe patient characteristics, causative factors, symptoms, location of stenosis, and management type. Results: In this study, 122 samples met the inclusion and exclusion criteria. LSS was mainly found in patients aged 60-69 years (33.6%) and in women (59%). Most LSS patients had obesity (BMI category I, 32%). Many LSS patients were housewives (42.62%) and reported light work activity (63.1%). The most common cause of LSS was degenerative factors (59%). The main symptom experienced by LSS patients was lower back pain (94.3%), frequently accompanied by radicular pain (79.5%). The most common location of stenosis was L4-L5 (43.4%). Most LSS patients in this study were managed both conservatively and operatively (70.5%). Conclusion: These findings contribute to a better understanding of LSS prevalence and distribution among patients. Further multicenter studies are needed to establish a comprehensive national LSS profile.